2014
DOI: 10.2337/dc13-0933
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obstructive Sleep Apnea in Rapid Eye Movement Sleep With Reduced Glycemic Control in Type 2 Diabetes: Therapeutic Implications

Abstract: OBJECTIVESeverity of obstructive sleep apnea (OSA) has been associated with poorer glycemic control in type 2 diabetes. It is not known whether obstructive events during rapid eye movement (REM) sleep have a different metabolic impact compared with those during non-REM (NREM) sleep. Treatment of OSA is often limited to the first half of the night, when NREM rather than REM sleep predominates. We aimed to quantify the impact of OSA in REM versus NREM sleep on hemoglobin A1c (HbA1c) in subjects with type 2 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
189
3
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(206 citation statements)
references
References 34 publications
(40 reference statements)
4
189
3
10
Order By: Relevance
“…The severity of OSA has been reported to associate with poor glycemic control in patients with T2DM [7,[9][10][11]. However, in our study, while we found a significant association between the severity of OSA and HbA1c level in non-diabetic subjects, this association was not significant in subjects with T2DM.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The severity of OSA has been reported to associate with poor glycemic control in patients with T2DM [7,[9][10][11]. However, in our study, while we found a significant association between the severity of OSA and HbA1c level in non-diabetic subjects, this association was not significant in subjects with T2DM.…”
Section: Discussioncontrasting
confidence: 95%
“…Therefore, in patients with OSA, REM sleep is typically associated with an increased frequency of obstructive events that are often prolonged and accompanied by severe oxygen desaturation [16][17][18]. Grimaldi et al reported that REM AHI but not non-REM AHI was associated with HbA1c level in patients with T2DM [11]. However, in that study, the proportion of patients with severe OSA; i.e., AHI ≥ 30, was only 30% and the majority had mild to moderate OSA.…”
Section: Discussionmentioning
confidence: 99%
“…4 OSA in adults is associated with increased risk of insulin resistance (IR), 5,6 MetSyn, 7,8 and T2DM 6,7 and poorer glycemic control in adults with existing T2DM. [9][10][11] Similarly, OSA prevalence is greater among adults with T2DM 12 vs community-based cohorts. 13 Treating OSA in adults using CPAP improves IR, although the impact on glycemia is more unpredictable.…”
mentioning
confidence: 99%
“…Остается открытым вопрос об опти-мальной длительности СиПАП-терапии в течение отдель-но взятой ночи и количестве необходимых ночей. В недавнем исследовании показано, что гликемия у боль-ных СД2 нарушается в ответ на обструктивные апноэ и гипопноэ в REM-сне, но не во время NREM-сна [16]. На основе предсказательной модели, выстроенной на 115 пациентах с обоими заболеваниями, даются оценки, согласно которым 4-часовая СиПАП-терапия оставит 60% обструктивных эпизодов во время REM-сна без лечения, а HbAc1 снизится на 0,25%.…”
Section: обсуждение сипап и углеводный обменunclassified
“…В частности, это связано с более высокой представленностью REM-сна в утренние часы, уже после того, как пациент снимает маску СиПАП. В то же время при 7-часовой длительности лечение охва-тит 85% REM-сна и приведет к снижению HbA1c на 1% [16]. С нашей точки зрения, это означает, что подгруппе больных СОАС с СД2 необходим собственный минималь-ный порог приверженности к терапии, возможно, даже больший, чем в нашем исследовании.…”
Section: обсуждение сипап и углеводный обменunclassified